Association between health behaviours and the COVID-19 vaccination: risk compensation among healthcare workers in Taizhou, China. Issue 1 (31st December 2022) - Sun, Liang-Xue; Chen, Li-Li; Chen, Wei-Ying; Zhang, Mei-Xian; Yang, Meng-Ge; Mo, Li-Cai; Zhu, Jing-Jing; Tung, Tao-Hsin; Li, Fei-Ping
ABSTRACT: This study is conducted to explore the association between health behaviors and the COVID-19 vaccination based on the risk compensation concept among health-care workers in Taizhou, China. We conducted a self-administered online survey to estimate the health behaviors among the staff in a tertiary hospital in Taizhou, China, from May 18 to 21 May 2021. A total of 592 out of 660 subjects (89.7%) responded to the questionnaire after receiving an e-poster on WeChat. Subjects who had been inoculated with the COVID-19 vaccine were asked to mention the differences in their health behaviors before and after the vaccination. The results showed that there were no statistical differences in health behaviors between vaccinated and unvaccinated groups, except in terms of the type of gloves they used (62.8% in the vaccinated group and 49.2% in the unvaccinated group, p = .048). Subjects who received earlier COVID-19 vaccinations exhibited better health behaviors (22.40% increased for duration of wearing masks ( P = .007), 25.40% increased for times of washing hands ( P = .01), and 20.90% increased for times of wearing gloves ( P = .01)). Subjects also revealed better health behaviors (washing hands, wearing gloves, and wearing masks) after vaccination compared to that before. In conclusion, concept of risk compensation was not applied in our findings. The health behaviors did not reduce after the COVID-19 vaccination, which even may improve health behaviors among health-care workers in the hospital setting.